Superficial implementation of religious moderation in Islamic educational management - Chusnul Chotimah; Saifuddin Zuhri Qudsy; Mirna Yusuf (Cogent Education)
This study examines of religious moderation in Indonesia educational institutions, focusing on its cognitive dimension. This focus frequently results in a superficial understanding of religious moderation, depicting it more as a theoretical concept than a transformative force in shaping one’s character. The study serves as a complementary investigation to previous inquiries by addressing the often-neglected contradictory aspects. Employing qualitative research methodologies, the study gathered data from diverse online news outlets, digital journals, and interviews with religious educators. The findings within educational institutions shed light on the top-down execution of religious moderation policies, coupled with an implementation that predominantly remains confined to the textual realm. Three primary factors elucidate the superficial nature of religious moderation. Firstly, the material’s superficiality, presented in a textual learning format, is a direct consequence of top-down policies. Religious moderation education conforms to predetermined programs within the constrained timeframe of Islamic Religious Education classes, lacking practical application beyond the classroom. Secondly, the material concerning religious moderation in educational institutions lacks integration with the prevailing school culture. Thirdly, the repercussions of superficial religious moderation become apparent in the cultivation of moderation values that lack contextualization with social realities, resulting in heightened intolerance, instances of violence within the educational sector, and an increased susceptibility among students to adopt fanatical attitudes.